Kontribusi Gender di Desa Boti Kabupaten Timor Tengah Selatan - Novi Theresia Kiak; Nikson Tameno (Kadiri University, 2022)
This study aimed to determine the gender contribution of farmers' wives in the domestic and public sectors in increasing household income. This research was conducted in Boti Village, Timor Tengah Selatan Regency, Nusa Tenggara Timur Province, with ten farmers' wives as key informants. The study employed a descriptive qualitative approach. The data collection techniques were observation, interviews, and documentation. The study results indicated that the farmer's wife had contributed significantly to her family. The wives helped husbands increase their household income by working in the public sector, and they also played a role in the domestic industry. They played dual roles to prosper their families, as housewives and working wives. Fokus dalam penelitian ini adalah Kontribusi gender dari para istri petani Desa Boti yang bekerja di sektor domestik dan sektor publik untuk meningkatkan pendapatan keluarga di Desa Boti Kabupaten Timor Tengah Selatan. Penelitian dilaksanakan di Desa Boti Kabupaten Timor Tengah Selatan. Dengan menggunakan pendekatan deskriptif kualitatif. Dengan teknik observasi, wawancara dan dokumentasi.Hasil penelitian ini menunjukkan bahwa kontribusi gender istripetani di Desa Boti Kabupaten Timor Tengah selatan, telah banyak memberikan kontribusi yang cukup bagi keluarganya, para istri petani di Desa Boti turut andil dalam membantu suami untuk meningkatkan pendapatan rumah tangganya dengan bekerja di sektor publik serta para istri petani juga berperan dalam sektor domestik guna untuk mensejahterakan keluarganya dengan peran ganda, menjadi ibu rumah tangga dan mencari nafkah membantu ekonomi keluarga.